Preschoolers’ mother-reported and caregiver-teacher-reported behavioral and emotional problems according with a child’s birth order - Jusienė, Roma; Kuzminskaitė, Monika (Psichologija, 2017)
Birth order (or the sequence of the siblings according with their birth within one family) is a phenomenon discussed and researched starting with as long ago as writings of Sigmund Freud and Alfred Adler. Yet it is still not possible to argue beyond the reasonable doubt whether the birth order has any direct or indirect influence on individual personality development and later personal and social achievements in life. Multiple attempts in the area have been made with differing results; the methods of the analysis have been criticized, so even today no sound and reliable arguments can be presented for the conclusion on this issue. What we have achieved is definitely an understanding that the phenomenon is very complex in nature, there are many factors that need to be considered together, and their influence on each other is still something to be untangled. Thus, birth order continues to remain a focus of the ongoing research. The purpose of this study is to increase the knowledge of the various consequences that changes within a family (as identified by the birth order of children in the family) may have on personal development and to identify whether the emotional and behavioral problems of Lithuanian preschool children are related to their birth order. We analyzed data of 338 Lithuanian four-year-old children (174 girls and 164 boys). Mothers and caregiver-teachers have rated the children’s behavioral and emotional problems with CBCL/1½-5 and C-TRF (Achenbach & Rescorla, 2000). Children were grouped according with their birth order (reported by mothers) into three groups: first-borns (N – 51), the only children (N – 134), and the youngest children (N – 140). The group of middle-born children (N – 13) was too small for further analysis. The results showed that firstborn children were rated as having more emotional and behavioral problems by their mothers than the youngest children. Kindergarten teachers’ reports on children’s emotional and behavioral problems did not differ in various birth order groups. We conclude that it is possible that, according to Alfred Adler, “dethroned” children (who were the only child and became the first born after a younger sibling was born) display more emotional and behavioral problems only towards their parents or in the home environment, and that birth order as an easily observable factor could be part of the complex intrafamily continuum of social influences and relationships.
Keywords: birth-order; behavioral problems; emotional problems; preschool age